2017
DOI: 10.3329/jbau.v15i2.35072
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria parasites in indigenous chickens and ducks in selected districts of Bangladesh

Abstract: Avian haematozoans are important pathogens of birds causing asymptomatic to fatal infections. The present study was undertaken to investigate the prevalence and associated risk factors of malaria parasite infections in domestic chickens and ducks in three localities namely Mymensingh, Tangail and Netrokona districts in Bangladesh. In total, 474 blood smears (266 chickens and 208 ducks) were screened for haemoprotozoan infection during the period from March, 2016 to February, 2017. Blood samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
5
4
3
Order By: Relevance
“…In addition, several similar studies have reported Plasmodium species in some parts of the world as the most frequently found avian haemosporidian parasite in free-range chickens in their respective study areas [9,33,42]. The findings of the present study are inconsistent with Gimba et al [21], Opara et al [32] and Hassan et al…”
Section: No Of Chickens Examinedcontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, several similar studies have reported Plasmodium species in some parts of the world as the most frequently found avian haemosporidian parasite in free-range chickens in their respective study areas [9,33,42]. The findings of the present study are inconsistent with Gimba et al [21], Opara et al [32] and Hassan et al…”
Section: No Of Chickens Examinedcontrasting
confidence: 99%
“…[4] and Ogbaje et al [2], who also reported a higher prevalence of haemosporidian parasites in males compared to female free-range chickens in Owerri, Maiduguri, Nassarawa and Markudi, respectively, in Nigeria. The finding of this study also confirmed previous reports by Sabuni et al [34] in Kenya, Hasan et al [9] in Bangladesh, Etisa et al [33] in Ethiopia, which also reported a high prevalence of haemosporidian parasites in free-range chicken cocks in their respective studies compared to the hens. In contrast, Naqvi et al [44] in Pakistan and Nath and Bhuiyan [25] in Bangladesh indicated that the hens have higher prevalence rates of infection with avian haemosporidian parasites compared to the cocks in scavenging chickens.…”
Section: No Of Chickens Examinedsupporting
confidence: 92%
See 1 more Smart Citation
“…Plasmodium species (9.4%) was the most common haemosporidian in village hens, confirming the findings of other researchers who found Plasmodium species to be the most common haemosporidian infection in scavenging birds [4,6,8,19,21,32,37]. However, the Plasmodium prevalence rate in this study is lower than 11.4% in Maiduguri [11], 12.0% in Sokoto [40], 33.3% in Owerri [27], and 32.0% in Ibadan [33] of Borno, Sokoto, Imo, and Oyo States respective in Nigeria.…”
Section: Microfilariasupporting
confidence: 88%
“…Previous reports have indicated more likelihood of female domesticated poultry species being more exposed to arthropods during incubation compared to the males in Nigeria [36][37][38] and in Ethiopia [39]. This finding contradicts the sex-specific prevalence of avian haemoparasites reported in chickens where prevalence is reported significantly higher in cocks than in hens [33,34,40]. The reasons were attributed to the abundance of predilection sites and larger surface areas (larger comb and wattles in male compared to female)…”
Section: Discussionmentioning
confidence: 93%